2021
DOI: 10.1007/s00439-021-02364-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of autosomal dominant and recessive TMC1-associated hearing loss

Abstract: TMC1 is a causative gene for both autosomal dominant non-syndromic hearing loss (DFNA36) and autosomal recessive non-syndromic hearing loss (DFNB7/11). To date, 125 pathogenic variants in TMC1 have been reported. Most of the TMC1 variants are responsible for autosomal recessive hearing loss, with only 8 variants reported as causative for DFNA36. Here, we reported the prevalence of TMC1-associated hearing loss in a large non-syndromic hearing loss cohort of about 12,000 subjects. As a result, we identified 26 p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Only 1 of the 11 affected individuals in the present study had balance problems. This finding is in line with previous studies that found no vestibular symptoms associated with TMC1-associated HL cases [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Only 1 of the 11 affected individuals in the present study had balance problems. This finding is in line with previous studies that found no vestibular symptoms associated with TMC1-associated HL cases [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…All the affected individuals with recessively inherited TMC1 variants displayed severe-to-profound congenital hearing loss associated with down-sloping audiograms, where higher frequencies are the most severely affected. This is consistent with previous publications demonstrating that pathogenic recessive TMC1 variants cause moderate-to-profound hearing loss [ 17 , 18 , 19 , 20 ]. The individuals affected with ADSNHL displayed progressive postlingual sensorineural hearing loss that led to profound deafness and the need for CIs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…TMC1 gene mutations causing human deafness are divided into two categories: those referred to as DFNA36 (OMIM # 606705), which are autosomal dominant, and those termed DFNB7 (OMIM # 600974), which are autosomal recessive. Nonsense and frameshift mutations of TMC1 predicted to cause a loss of normal protein function through protein truncation are often detected in DFNB7/11 patients (Kraatari‐Tiri et al, 2022 ; Nishio & Usami, 2022 ). Our patient carried a break point in intron 8 of TMC1 , which interrupted the open reading frame.…”
Section: Discussionmentioning
confidence: 99%
“…The influx of Ca 2+ can modulate the activation and adaptation of the transducer current in a concentrationdependent manner 44,67 . However, the involvement of calcium in fast adaption of MET remains under debate [68][69][70] To date, over 100 pathogenic variants in TMC1 have been reported 71,72 , with only 8 of them responsible for DFNA36 (M113I, F313S, S320R, G417R, M418K, D543N, D572N and R759H).…”
Section: Ef-hand In Sensing Systemsmentioning
confidence: 99%